Structural brain preservation: a potential bridge to future medical technologies - McKenzie, Andrew T.; Zeleznikow-Johnston, Ariel; Sparks, Jordan S.; Nnadi, Oge; Smart, John; Wiley, Keith; Cerullo, Michael A.; de Wolf, Aschwin; Minerva, Francesca; Risco, Ramón; Church, George M.; de Magalhães, João Pedro; et al. (Frontiers in Medical Technology, 2024)
When faced with the prospect of death, some people would prefer a form of long-term preservation that may allow them to be restored to healthy life in the future, if technology ever develops to the point that this is feasible and humane. Some believe that we may have the capacity to perform this type of experimental preservation today—although it has never been proven—using contemporary methods to preserve the structure of the brain. The idea is that the morphomolecular organization of the brain encodes the information required for psychological properties such as personality and long-term memories. If these structures in the brain can be maintained intact over time, this could theoretically provide a bridge to access restorative technologies in the future. To consider this hypothesis, we first describe possible metrics that can be used to assess structural brain preservation quality. We next explore several possible methods to preserve structural information in the brain, including the traditional cryonics method of cryopreservation, as well as aldehyde-stabilized cryopreservation and fluid preservation. We focus in-depth on fluid preservation, which relies on aldehyde fixation to induce chemical gel formation in a wide set of biomolecules and appears to be a cost-effective method. We describe two theoretical recovery technologies, alongside several of the ethical and legal complexities of brain preservation, all of which will require a prudent approach. We believe contemporary structural brain preservation methods have a non-negligible chance of allowing successful restoration in the future and that this deserves serious research efforts by the scientific community.